2020
DOI: 10.1186/s12931-020-1314-5
|View full text |Cite
|
Sign up to set email alerts
|

Frequent mutation of hypoxia-related genes in persistent pulmonary hypertension of the newborn

Abstract: Aims: Persistent pulmonary hypertension of the newborn (PPHN) is characterized by sustained high levels of pulmonary vascular resistance after birth with etiology unclear; Arterial blood oxygen saturation of Tibetan newborns at high latitudes is higher than that of Han newborns at low latitudes, suggesting that genetic adaptation may allow sufficient oxygen to confer Tibetan populations with resistance to pulmonary hypertension; We have previously identified genetic factors related to PPHN through candidate ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…They found that 3 SNPs (rs192759073, rs1047883 and rs2229589) in CPS1 and one SNP (rs1044008) in NOTCH3 were significantly associated with PPHN (P<0.05). Wang et al ( 14 ) found that the p.E317K and p.P777S variants in the tubulin tyrosine ligase-like family member 3 ( TTLL3 ) gene and the p.E1071D variant in the integrin subunit alpha M ( ITGAM ) gene were associated with PPHN in high altitude areas (Tibet and Han in China). Recently, we found that the rs17034984 variant in the EPAS1 gene, which encodes either the endothelial PAS domain-containing protein 1 or the HIF-2α protein was a possible genetic susceptibility locus associated with PPHN ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…They found that 3 SNPs (rs192759073, rs1047883 and rs2229589) in CPS1 and one SNP (rs1044008) in NOTCH3 were significantly associated with PPHN (P<0.05). Wang et al ( 14 ) found that the p.E317K and p.P777S variants in the tubulin tyrosine ligase-like family member 3 ( TTLL3 ) gene and the p.E1071D variant in the integrin subunit alpha M ( ITGAM ) gene were associated with PPHN in high altitude areas (Tibet and Han in China). Recently, we found that the rs17034984 variant in the EPAS1 gene, which encodes either the endothelial PAS domain-containing protein 1 or the HIF-2α protein was a possible genetic susceptibility locus associated with PPHN ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…The correlation analysis of point mutations and gene levels was completed with reference to a previously published study [ 61 ]. In short, We first calculated the groups carrying rare variants, including heterozygous or homozygous mutations, referring to the gnomAD database [ 62 ] containing large-scale, whole exomes (123,136 samples, including 8624 people of East Asian ethnicity) and whole-genome sequencing samples.…”
Section: Methodsmentioning
confidence: 99%
“…The most common cause of transient PAH in neonates is persistent pulmonary hypertension of the newborn (PPHN), a failure of immediate postnatal cardiopulmonary transition with an annual incidence of 30.1 cases/million 1 , 35 . The genetic aetiology of PPHN is unclear; although potential susceptibility variants have been recently reported in CPS1 , NOTCH3 , SMAD9 and the hypoxia-related genes TTLL3 and ITGAM , these remain to be independently validated 36 , 37 .…”
Section: Associated and Syndromic Forms Of Pulmonary Arterial Hyperte...mentioning
confidence: 99%